PH-responsive hydrogel loaded with insulin as a bioactive dressing for enhancing diabetic wound healing. (15th November 2021) - Li, Zuhao; Zhao, Yue; Liu, He; Ren, Ming; Wang, Zhonghan; Wang, Xianggang; Liu, Hou; Feng, Yubin; Lin, Quan; Wang, Chenyu; Wang, Jincheng
Graphical abstract: Highlights: Reversible dynamic bonds give hydrogels injectable and self-healing properties. Insulin released from the hydrogel in a pH-responsive mode. Bioactive dressings improve healing and peripheral neuropathy of diabetic wounds. Abstract: The healing of diabetic foot ulcers (DFUs) is a major challenge for clinical treatment because of the hyperglycemic and acidic microenvironment in the wound area. In this study, a self-healing, injectable, and pH-responsive hydrogel was synthesized by N-carboxyethyl chitosan (N-chitosan), hyaluronic acid–aldehyde (HA-ALD), adipic acid dihydrazide (ADH) through the formation of the reversible dynamic bonds, acylhydrazone and imine bonds. The presence of the acylhydrazone bond characterizes the hydrogel pH-responsive property. In this study, the insulin glargine was successfully incorporated into the hydrogel, allowing its sustained and pH-responsive releasing from the hydrogel for up to 14 days. The hydrogel presented good compatibility and pore structure, and the insulin released from the hydrogel maintained its original bioactivity. Full thickness wounds were established on the feet of diabetic rats to evaluate the therapeutic effect of the dressing. The results revealed that the bioactive insulin-loaded hydrogel dressing shortened the inflammatory phase, enhanced granulation tissue formation, promoted collagen deposition, accelerated re-epithelialization and neovascularization, and postponed or even improved peripheral neuropathy, thus, significantly accelerated DFUs healing. Our findings showed that the insulin-loaded hydrogels had promising potential as a multifunctional bioactive wound dressing for enhancing DFUs healing.